Analysis of the Effect of Free Cash Flow, Liquidity and Profitability on Debt Policy - Fitriyadi, Nanok; Pakata, Rosmiati (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The purpose of this study was to determine the effect of free cash flow, liquidity and profitability on debt policy in chemical manufacturing companies listed on the Indonesia Stock Exchange for the period 2016 – 2020. The number of research samples is 10 chemical sub-sector companies on the Indonesia Stock Exchange. The sampling technique used is purposive sampling method. Multiple linear regression analysis was used to process the data using SPSS Version 26. The results of the study based on the t-test showed that free cash flow had a negative and insignificant effect on debt policy, liquidity and profitability had a negative and significant effect on debt policy. Meanwhile, based on the Free Cash Flow F test, liquidity and profitability have a significant effect on debt policy simultaneously.